Public Ownership And Firm Value: Mediation Role Of Carbon Emissions Disclosure - Suwandi Ng; Robert Jao; Fransiskus E. Daromes; Monica (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
Carbon emissions and the risk of climate change have a great impact on the environment and company performance. This study provides empirical evidence that public ownership encourages the disclosure of carbon emissions and their subsequent impact on firm value. In contrast to previous studies related to the driving factors for carbon emission disclosure which only focused on the role of directors and aspects of company characteristics, this study considers the ownership aspect in this case public ownership in encouraging the disclosure of carbon emissions and its subsequent impact on firm value. The research data was obtained from the Financial Statements of 122 companies listed on the Indonesia Stock Exchange for the observation period from 2015 to 2019. The data were selected using the purposive sampling method. The results of this study indicate that public ownership has a positive and significant effect on the disclosure of carbon emissions while a company is owned by the public increases firm value but not significantly. The results also show that disclosure of carbon emissions plays a role in mediating public ownership of the value of the company. The implications of this study confirm the stakeholder theory that companies should protect stakeholders by implementing environmental management and disclosing sustainability reports that provide information about their social, economic, and environmental performance.